Comparison of desmoglein 1 and 3 enzyme‐linked immunosorbent assay and direct immunofluorescence for evaluation of immunological remission in pemphigus vulgaris. (1st January 2014) - Daneshpazhooh, M.; Kamyab, K.; Kalantari, M.‐S.; Balighi, K.; Naraghi, Z. S.; Shamohammadi, S.; Mortazavizadeh, S. M.‐A.; Ramezani, A.; Chams‐Davatchi, C.
Summary: Background: Drug withdrawal is the ultimate goal in the management of patients with pemphigus. Direct immunofluorescence (DIF) has long been considered the gold‐standard test to predict immunological remission in pemphigus vulgaris (PV); however, there have been no comparisons between DIF and antidesmoglein (anti‐Dsg) ELISA. Aim: To compare anti‐Dsg ELISA with DIF in patients with PV for evaluation of immunological remission. Methods: The study enrolled 46 patients with PV who had absence of any lesion, and had a daily prednisolone dosage of ≤ 10 mg without adjuvant drug treatment in the preceding 6 months. Biopsy specimens were taken from patients and processed for DIF. Intercellular deposition of IgG and/or C3 was considered positive. Serum samples were also collected for anti‐Dsg1 and anti‐Dsg3 ELISA, and an ELISA index value of > 20.0 was considered positive. Results: DIF and anti‐Dsg ELISA were positive for 11 (23.9%) and 18 patients (39.1%), respectively. Anti‐Dsg ELISA had a sensitivity of 100%, a specificity of 80%, a positive predictive value of 61.1% and a negative predictive value of 100%. Conclusions: The high sensitivity of anti‐Dsg ELISA proves that this simple serological test is a good substitute for DIF for evaluation of immunological remission in PV. As none of the DIF‐positive patients was anti‐Dsg‐negative, it is possible that during the course of immunological remission, results for DIF may become negative before the results for Dsg ELISA do so. Abstract : Click here for the corresponding questions to this CME article.